27 Al NMR/MRI Studies of the Transport of Granular Al 2 O 3 - Koptyug, Igor V.; Lysova, Anna A.; Khomichev, Alexey V.; Sagdeev, Renad Z. (Diffusion Fundamentals, 2007)
The NMR/MRI techniques are applicable to the studies of motion of granular solids, providing information on the velocities, effective diffusivities and correlation times of the moving particles. The studies of transport of granular solids reported to-date are based on the detection of the 1H NMR signal of the liquid phase of liquid-containing solid materials. Yet, the solid phase of many granular solids contains magnetic nuclei, providing in principle an opportunity to study motion of such solids by directly detecting the NMR signal of the solid phase. In this paper, we demonstrate that this can be performed with the use of conventional echo pulse sequences in combination with the conventional motion encoding schemes. The detection of the 27Al NMR signal of the Al2O3 powder was used to obtain velocity maps of the powder packed in a spinning cylinder, and to measure the velocity distribution (average propagator) for the gravity driven transport of the same powder in a vertical pipe.